PERINTISAN RUMAH BACA "SERA CENDEKIA" SEBAGAI UPAYA PENGEMBANGAN GENERASI GEMAR MEMBACA DI PERUMAHAN PURI KRAKATAU HIJAU CILEGON - Ratu Erlina Gentari; Kodriyah Kodriyah; Herman Wijaya (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
The main focus of this community service program is to provide socialization and pioneering of reading houses to children so that their love of reading grows, and that their love of reading becomes a necessity for seeking knowledge. This service activity was carried out at the Puri Krakatau Hijau Housing, Kotasari Village, Grogol District, Cilegon City, Banten Province. The condition of housing that does not have reading house facilities plus the location of the regional library is quite far, located in Cilegon City. This causes children to be reluctant to read, in addition, with the current Covid-19 pandemic condition which requires children not to leave the house or the surrounding environment. The Reading House "Sera Cendikia" is here to answer the problems that occur in the Puri Krakatau Hijau housing. The target to be achieved through this service program is the fulfillment of children's rights to education and so that children become fond of reading. The method used is the Glenn Doma Method, which is a method of teaching reading to children using flash cards so that children will have a sense of confidence, imagenative, and happyness. Education at the basic level is currently often neglected with information technology, even though it is precisely at the basic level that the role of learning begins to be applied, the results obtained are that there is an increase in learning outcomes with this method by 60% of learning.